Alvarado, J., F. Portocarrecro, C. Trivelli, e. Gonzales, F. Galarza y H. Venero. El financiamiento informal en el Perú. Lima: COFIDE, CEPES, IEP, 2001. - Blanco Hauchecorne, Flor de Esperanza (2001)
Esta reseña no presenta resumen.